Propriedade privada imobiliária urbana: espaço e campo na disputa entre proprietários e não proprietários - Juliano dos Santos Calixto (2018)
The present study develops from the problem of the dispute over the right to property from an inclusive point of view that also considers non-owners in the debate on the right to property. To understand the problem, we adopt a reconstructive perspective of the dispute over the right of real estate property. In the first place, such reconstruction is carried out from the field of Brazilian civil law, with the verification of the foundation of property in natural law and economic liberalism. Once this starting point is set, reconstruction continues with the diagnosis of the dispute with the perspective of urban law, which with the emergence of a new paradigm with the 1988 Constitution defends a new form of regulation of property rights. Then, the notion of spatialization of the dispute over property is raised from the concepts of right to the city and the production of space, emphasizing the importance of the spatial context to establish the concrete conflicts involving real estate. Finally, the externalized form of the property dispute is discussed in the context of the right to housing based on the field research that analysed four Urban Occupations of the Metropolitan Region of Belo Horizonte. The theoretical disputes and concepts discussed are related to the occupants' depositions and to the arguments raised in lawsuits involving the occupied areas. The reconstructive methodology combines a critical theoretical reading and empirical analysis, with the contribution of the field work fulfilled by interviews and the analysis of arguments in judicial decisions. The transcript of the interviews and the copies of the records were obtained from the data collected by the Urban Occupation Mapping Survey of the RMBH. The theoretical basis is organized in the concepts of field, by Bourdieu, right to the city and space, by David Harvey. The research aims to contribute to the theme by demonstrating that the construction of property rights occurs in concrete conflicts and for their better understanding it is necessary to spatialize the dispute, which includes to look at it from the point of view of non-owners.